Fertility preservation in young female cancer patients: development and pilot testing of an online decision aid - Ehrbar, Verena; Germeyer, Ariane (Journal of Adolescent and Young Adult Oncology, 2018)
Purpose: Impairment of fertility is a common sequela of successful cancer treatment. Therefore, fertility preservation (FP) should be discussed with all young cancer patients. Decisions about FP are challenging. Patients wish more specific support and the first results concerning the helpfulness of decision aids (DA) were promising. Aside from describing the process of development and the content of an online DA in German, the objective of this study was to pilot test users' satisfaction with the DA and its effect on knowledge about FP and decisional conflict (DC).Methods: In this prospective consecutive study, a control group (n = 20, fertility counseling) was followed by and compared with an intervention group (n = 20, counseling and additional use of the DA, developed by an interdisciplinary team) of recently diagnosed female cancer patients between 18 and 40 years.Results: Nearly all participants who applied the DA considered it helpful for decision-making and recommendable. Knowledge about FP was high with regard to FP techniques women went for. DC was moderate according to the mean score (M = 27.92, standard deviation = 13.27) and only in 20%, the score was above the threshold for high DC. There was no difference between the control and intervention group for knowledge and DC.Conclusion: The DA seems to serve as additional and well-accepted support tool in decision-making for patients and professionals. Referral to a reproductive specialist is crucial to warrant comprehensive information. These results need to be confirmed with the current ongoing randomized controlled study.
Gesehen am 29.07.2019
Online ahead of print: July 31, 2017